A comparison of the effects of different methodologies on the statistics learning profiles of prospective primary education teachers from a gender perspective - Anasagasti, Jon; Berciano, Ainhoa; Izagirre, Ane (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2023)
Over the last decades, it has been shown that teaching and learning statistics is complex, regardless of the teaching methodology. This research presents the different learning profiles identified in a group of future Primary Education (PE) teachers during the study of the Statistics block depending on the methodology used and gender, where the sample consists of 132 students in the third year of the PE undergraduate degree in the University of the Basque Country (Universidad del País Vasco/Euskal Herriko Unibertsitatea, UPV/EHU). To determine the profiles, a cluster analysis technique has been used, where the main variables to determine them are, on the one hand, their statistical competence development and, on the other hand, the evolution of their attitude towards statistics. In order to better understand the nature of the profiles obtained, the type of teaching methodology used to work on the Statistics block has been taken into account. This comparison is based on the fact that the sample is divided into two groups: one has worked with a Project Based Learning (PBL) methodology, while the other has worked with a methodology in which theoretical explanations and typically decontextualized exercises predominate. Among the results obtained, three differentiated profiles are observed, highlighting the proportion of students with an advantageous profile in the group where PBL is included. With regard to gender, the results show that women's attitudes toward statistics evolved more positively than men's after the sessions devoted to statistics in the PBL group.